EXPIRATION YEAR ACTIVE FAVORS CONCENTRIC (Fiep Bulletin - online, 2013)
Guidance on the breath within the academies during the concentric movements associated with the expiration of the exercise is increasingly scarce. Given this reality, the present study consisted of a prospective, descriptive and applied quantitative character, with the objective of evaluating the efficacy of active expiration associated with the concentric movement. The sample consisted of 47 volunteers, 25 females and 22 males with a mean age of 29.5 (± 12.08) years, bodybuilders. Data collection was based on a questionnaire, administered before and after the implementation of two specific physical exercises for strengthening the pectoralis major muscle and the quadriceps muscle group. Initially the volunteers performed the exercises the way they were used and then were instructed to carry them to the expiration active in the concentric phase. Of the total sample 71.74% reported not having received guidance on the part of the academy, as the realization of breath during the exercises, and 73.91% reported having more ease in performing those with active expiration. Another important observation was that 78.26% of the sample signaled the sensation of abdominal contraction during the execution of the exercises associated with active expiration. It was concluded that the performance of active expiration may contribute to the development of an optimization exercise and even, indirectly, stimulate contraction of the abdominal muscles.
Keywords: Exercises; Muscle contraction; breathing.